Analysis of the essential oil extract from the aerial parts of southernwood herb (Artemisia abrotanum L.) that grown in Iraq by GC/MS - Sarah S. Almahdawy; Ibrahim S. Abbas; Ashour H. Dawood (College of Pharmacy / Mustansiriyah University, 2018)
Objective: this research is to identify the chemical composition of essential oil of the aerial parts of A.abrotanum L. that grown in Iraq and used recently only for decorative purpose. Method: After collection of the aerial parts the essential oil extracted by hydro-distillation using Clevenger apparatus, then the oil are analyzed by GC/MS. Result: The obtained results show the presence of 14 compounds. The most important constituents are: Eucalyptol (1, 8-cineole), O-cymene, Camphor, Terpineol, Borneol, Longipinocarvone, Limonene, and Aromadendrene. Conclusion: This study analyzes the chemical constituents of the essential oil of A.abrotanum. The essential oil extracted by hydrodistillation then analyzed by GC/MS. 14 Compounds were identified. Due to good result obtained from the essential oil from this plant so further studies chemically and clinically of the active compounds is required.